Access to facility delivery and caesarean section in north-central Liberia: a cross-sectional community-based study. Issue 6 (31st October 2012) - Gartland, Matthew G; Taryor, Victor D; Norman, Andy M; Vermund, Sten H
Abstract : Objective: Rural north-central Liberia has one of the world's highest maternal mortality ratios. We studied health facility birthing service utilisation and the motives of women seeking or not seeking facility-based care in north-central Liberia. Design: Cross-sectional community-based structured interviews and health facility medical record review. Setting: A regional hospital and the surrounding communities in rural north-central Liberia. Participants: A convenience sample of 307 women between 15 and 49 years participated in structured interviews. 1031 deliveries performed in the regional hospital were included in the record review. Primary outcomes: Delivery within a health facility and caesarean delivery rates were used as indicators of direct utilisation of care and as markers of availability of maternal health services. Results: Of 280 interview respondents with a prior childbirth, only 47 (16.8%) delivered their last child in a health facility. Women who did not use formal services cited cost, sudden labour and family tradition or religion as their principal reasons for home delivery. At the regional hospital, the caesarean delivery rate was 35.5%. Conclusions: There is an enormous unmet need for maternal health services in north-central Liberia. Greater outreach and referral services as well as community-based education among women, family members and traditional midwives are vital to improve the timely utilisation of care.